Dielectric studies of dispersions of carbon nanotubes in liquid crystal 5CB - Koval'chuk, A.; Dolgov, L.; Yaroshchuk, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The frequency dependences of the imaginary ε″ and real ε′ parts of complex dielectric permittivity inherent to planarly aligned layers of nematic liquid crystals 5CB doped with multiwalled carbon nanotubes (CNT) were investigated in a wide range of frequencies (f = 10⁻²-10⁶ Hz) and CNT concentrations (c = 0-0.25 wt.%). It has been shown that the studied frequency range can be divided in three parts according to behavior of ε′ (f) and ε″ (f) curves. The low-frequency range (10⁻² < f < 10¹ Hz) reflects the near-electrode processes in the cell. The ratio ε″/ε′ used to characterize these processes sharply grows if the concentration of CNT exceeds 0.05 wt.%. The moderate frequency range (10¹ < f < 10⁵ Hz) corresponds to the alternating current conductivity, σАС. At the nanotubes concentration less than 0.025 wt.%, σАС does not depend on the frequency that implies its ionic origin. In its turn, at the c ≥ 0.025 wt.%, σАС is a power function of the frequency that is typical for electronic hopping mechanism. The transition from the ionic to electronic conductivity can be explained by the percolation theory with the critical concentration of nanotubes 0.031 wt.% and percolation parameter 2.5. The high-frequency range (10⁵ < f < 10⁶ ) is mainly attributed to dipole volume polarization. For c < 0.05 wt.% such polarization is well described by the Debye equation. The time of dielectric relaxation in this frequency range increases with nanotubes content. This is explained by effective interaction of nanotubes with 5CB molecules.